Successful Double DIEP Syngeneic Transplantation across Monozygotic Twins for Total Back Reconstruction. (29th November 2021) - Selber, Jesse C.; Kameni, Lionel; Torres, Keila; Mericli, Alex; Chu, Carrie; Schaverien, Mark; Largo, Rene; Butler, Charles; Gaber, Osama
Abstract : Background: A 56-year-old woman presented with an extensive sarcoma requiring nearly total back resection. She had limited donor sites for reconstruction because of a previous laparotomy, but presented with a significantly larger, identical twin. Cancer has traditionally been considered a contraindication for vascularized composite allotransplantation; however, immunosuppression is potentially avoidable between monozygotic twins. Methods: A preoperative genetic workup revealed 10/10 human leukocyte antigen homozygosity. Despite substantial phenotypic divergence in size and facial features, the sisters were genotypically identical. A two-stage, double deep inferior epigastric perforator transplant was planned for delayed reconstruction. At the first stage following the resection, an arteriovenous loop was performed to provide recipient vasculature to the back. At a second stage, the transplantation was performed. In addition, bilateral lumbar artery perforator flaps were created to reduce the length of the defect. Intraoperative steroid bolus and a short taper alone were used for immunosuppression. Results: The resection resulted in a 22 × 29-cm specimen down to the spine. After a 4-day interval for permanent pathologic evaluation, the transplant was successfully transferred between twins. Two arteries and six veins were anastomosed to establish perfusion. Postoperatively, there have been no episodes of rejection or flap compromise at last follow-up (>36 months). Conclusions: This case represents one of the few vascularized composite allotransplantations between monozygotic twins, and the only reported successful vascularized composite allotransplantation for a recurrent cancer diagnosis. Oncologic safety depended on 100 percent histocompatibility to avoid immunosuppression. Limited patient donor sites precluded total autologous coverage, and a substantial size discrepancy between the twins favored a transplant.